Prevalence of low back pain and associated risk factors among professional car drivers in Dhaka city, Bangladesh (South East Asia Journal of Public Health, 2013)
Low back pain (LBP) is common and affects most people at some point in their life. The exact cause of LBP among professional car drivers is still uncertain. Epidemiological studies of LBP have been performed among general populations and professional drivers in different countries; however the data on LBP in this professional category is scarce in Bangladesh. This paper investigates the prevalence of LBP among professional car drivers in Dhaka city and examines the relationship between back pain and years of driving, driving duration per day and the body weight of the drivers. A cross-sectional study was performed during December 2010 using a questionnaire and car drivers who experienced back pain for at least one day during the past 12 months were included in the study. The study demonstrated that 78% of car drivers reported LBP for at least one day during the past 12 months. The study also revealed age, daily and cumulative driving in drivers and stature are among the risk factors of LBP. Occupational health and safety management interventions should be implemented to prevent adverse health effects in professional car drivers.South East Asia J Public Health | Jan-June 2012 | Vol 2 Issue 1 | 60-62 DOI: http://dx.doi.org/10.3329/seajph.v2i1.15267